Pengembangan Produk Pie Durian sebagai Alternatif Pengolahan Buah Durian di Desa Ngembal, Kabupaten Pasuruan, Jawa Timur - Ananda, Safira Dea; Hidayah, Nabilah Lailiyatul; Ahfas, Akhmad (Wadah Inovasi Indonesia, 2024)
Durian is one of the fruits that has high economic potential in Indonesia, especially in areas that have durian orchards such as Ngembal Village. However, durian is often considered difficult to market directly due to limited durability and differences in consumer tastes. This study aims to develop durian processed products in the form of durian pie as an alternative to durian fruit processing in Ngembal Village. This product development is expected to increase the added value of durian fruit, expand the market, and provide economic opportunities for durian farmers in Ngembal Village. This research method uses field surveys and interviews with one of the village officials in the economic division and community leaders in the UMKM sector as expert informants, followed by training. The results of this training are expected to expand the knowledge and skills of the Ngembal Village community in the field of processing local food ingredients into innovative culinary products and increase the economic value of natural resources, and support the tourism industry in the culinary field.